ANALISIS BUKU GLOBALISASI (JALAN MENUJU KESEJAHTERAAN) DAN KAITANNYA DENGAN PEMBELAJARAN IPS - Supriyanto, Supriyanto; Isbandiyah, Isbandiyah (LP4MK STKIP PGRI Lubuklinggau, 2023)
This writing aims to analyze the content of the book “Globalization: Road to Prosperity” and its relevance to social studies education, particularly in preparing social studies teachers to equip themselves as educators teaching social studies from a global perspective. The qualitative method is employed with a literacy study approach. Based on the analysis results, it can be concluded that the book “Globalization: Road to Prosperity” is more applicable to developed countries, while for developing countries, including Indonesia, it is more of a discourse, indicating that although we are in the era of globalization, entering it still requires a considerable amount of time. One notable agreement is that a statement in this book mentions,